Sinus thrombectomy for purulent cerebral venous sinus thrombosis utilizing a novel combination of the Trevo stent retriever and the Penumbra ACE aspiration catheter: the stent anchor with mobile aspiration technique. (27th May 2015) - Mascitelli, Justin R; Pain, Margaret; Zarzour, Hekmat K; Baxter, Peter; Ghatan, Saadi; Mocco, J
Abstract : Intracranial complications of sinusitis are rare but life threatening. We present a case of a 17-year-old woman with sinusitis who deteriorated over the course of 12 days from subdural empyema and global purulent cerebral venous sinus thrombosis. The patient was managed with surgery and mechanical thrombectomy utilizing a novel 'stent anchor with mobile aspiration technique', in which a Trevo stent retriever (Stryker) was anchored in the superior sagittal sinus (SSS) while a 5 MAX ACE reperfusion catheter (Penumbra) was passed back and forth from the SSS to the sigmoid sinus with resultant dramatic improvement in venous outflow. The patient was extubated on postoperative day 3 and was discharged with minimal lower extremity weakness on postoperative day 11. This is the first report using the Trevo stent retriever for sinus thrombosis. It is important to keep these rare complications in mind when evaluating patients with oral and facial infections.